2009
DOI: 10.1167/iovs.08-2927
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolites from Young Human Lenses and the Photooxidation of Ascorbic Acid by UVA Light

Abstract: The filter compounds present in human lenses can absorb UVA light and cause the oxidation of ascorbic acid in the presence and absence of oxygen, possibly initiating the glycation of lens proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Lens receives UV light (UVA and UVB) through the cornea. It is known that kynurenines are photosensitizers and they can oxidize ascobate [46]. Whether such oxidation occurs in low oxygen environment is not known, but it is likely.…”
Section: Discussionmentioning
confidence: 99%
“…Lens receives UV light (UVA and UVB) through the cornea. It is known that kynurenines are photosensitizers and they can oxidize ascobate [46]. Whether such oxidation occurs in low oxygen environment is not known, but it is likely.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution magic angle spinning proton NMR spectroscopy of ocular tissues revealed that GSH is present at much higher concentrations in the lens (Kryczka et al, 2014). GSH can react with free radicals and other oxidants generated by the formation of singlet oxygen ( 1 O 2 ) from the interaction between ultraviolet photons and tryptophan residues on the proteins (Ortwerth et al, 2009) and can also react with the oxidized form of ascorbate, dehydroascorbate, to regenerate ascorbate (Sasaki et al, 1995). The resulting oxidized glutathione (GSSG) is reduced back to GSH by NADPH, produced by residual metabolic activity (the pentose phosphate shunt) in the lens (Ganea and Harding, 2006).…”
Section: Antioxidants and Other Oxidation Limiting Mechanisms In The mentioning
confidence: 99%
“…The part of the solar spectrum that reaches and becomes absorbed by lens is thus dominated by UVA and the short wavelength segment of the visible spectrum. Whereas the detrimental effect of UVB is well documented in the literature, UVA seems less damaging [7,15,27] and may even bleach lens chromophores [28,29]. The effects of irradiation with visible light have not been described in the literature but since the aged human lens absorbs a great proportion of short wavelength visible light it is very relevant to examine this part of the electromagnetic spectrum for potentially hazardous effects.…”
Section: Introductionmentioning
confidence: 99%